Question of Leadership : Are There Any Potential Downsides to Emotional Intelligence for Executives, And If So, What Are They - Dess, Robert Hicks. Gregory G. (Center for Creative Leadership, 2008)
Emotional intelligence (EI) has become a popular concept in management practice and literature in recent years. The leading proponent of EI, Daniel Goleman, defines EI as the capacity for recognizing one's own emotions and those of others.